Is the function of the HBeAg really unknown? - Milich, David R. (Hum Vaccin Immunother, 2019)
The immune response to the hepatitis B virus (HBV) vaccine in newborns of hepatitis B e antigen (HBeAg)-positive or HBeAg-negative mothers is the subject of Huang et al. The authors report no correlation between the HBeAg status of the mothers/cord blood and the newborns immune response to the vaccine, but, unfortunately, draw unfounded conclusions regarding the tolerogenic potential of in utero exposure to HBeAg. In this reply, I address the possible influence of in utero exposure to the HBeAg, and briefly review other characteristics of the HBeAg, that may promote HBV chronicity. I argue that the function of HBeAg should no longer be considered “unknown” and that immunotolerance/immunomodulation represent the dominant functions of the HBeAg in viral–host interactions.